(untitled) (Research, Society and Development, 2022)
The objective of this study was to assess the risk factors for cardiovascular diseases in nurses working alternate shifts in public hospitals in Maceió, Alagoas, Brazil. This is a re-analysis article of a data cut from the Master’s dissertation "Evaluation of Electrocardiographic Changes among Nurses Working in Alternating and Fixed Shifts". The results were: 1) sociodemographic characteristics: predominance of young, married and female professionals, 2) lifestyle: considerable rate of overweight and obesity, but the consumption of alcohol and tobacco was low, 3) work-related characteristics: predominance of professionals between 6 and 10 years in the profession and in shift work and that performed double shifts, 4) assessment of blood pressure: significant amount with hypertension. As a conclusion of the study, it was found that nurses, due to the characteristics and nature of their work, are subject to several risk factors that contribute to an increase in cardiovascular diseases.